Model Pendidikan Minat Bakat Melalui Self-Efficacy di Sekolah - Humairah, Intan; Reihannah, Reihannah; Fitriana, Dedek Dhea; Safitri, Revi (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2024)
This study seeks to examine the correlation between students' interests and capabilities and their degree of self-efficacy in high school. The main objective is to establish educational models that enhance self-efficacy. Data was obtained from students and instructors at Lhoksukon Senior High School 1 using a comprehensive method that including questionnaires and interviews. The investigation reveals a favorable association between students' interests, abilities, and self-efficacy. Evidence has shown that the assistance provided by instructors and the overall school atmosphere has a crucial role in enhancing students' belief in their own abilities. The suggested educational approach prioritizes the incorporation of students' interests and skills into the curriculum and learning process in order to enhance their self-efficacy. The practical consequence of this study is the creation of educational practices that are comprehensive and focused on nurturing students' whole potential. These results provide significant additions to our knowledge of the connections between students' interests, abilities, and self-efficacy. They also offer guidance for improving educational procedures.